Diabetic Foot Ulcer Among Adults Attending Follow-Up Diabetes Clinics in Wolaita Zone, Southern Ethiopia: An Unmatched, Case-Control Study - Lielt Gebreselassie Gebrekirstos, MSc (Current Therapeutic Research, 2022)
ABSTRACT: Background: Diabetic foot ulcer is a major public health problem, and among the leading causes of this complication in Ethiopian patients with diabetes. Despite the magnitude of this problem, data regarding the determinants of diabetic foot ulcers are limited. Objective: This study aimed to assess the determinants of diabetic foot ulcers among adults attending follow-up visits in diabetes clinics in the Wolaita Zone, southern Ethiopia. Methods: An institution-based case-control study was done from September 10 to December 28, 2020, in southern Ethiopia. We recruited 137 patients with diabetic foot ulcers and 408 patients without any diabetic foot ulcers using a consecutive sampling method. EpiData version 3.1.1 (EpiData Association, Odense, Denmark) and SPSS version 25 (IBM-SPSS Inc, Armonk, New York) were used for data entry and analysis. Descriptive statistics were calculated followed by a multivariate logistic regression analysis. Results: Having a low wealth index (adjusted odds ratio [AOR] = 2.6; 95% CI, 1.177–5.662); being obese (AOR = 3.6; 95% CI, 1.380–9.547; P = 0.003), being overweight (AOR = 3.1; 95% CI, 1.480–6.436; P = 0.009), having peripheral neuropathy (AOR = 3.9; 95% CI, 1.641–9.430; P = 0.002), living with diabetes for >10 years (AOR = 2.3; 95% CI, 1.191–4.475; P = 0.013), and practicing poor diabetic foot self-care (AOR = 6.0; 95% CI, 3.156–11.312; P = 0.000) were significantly associated with having a diabetic foot ulcer. Conclusions: This study suggests there is a need for education and counseling of patients on decreasing weight and improving foot-care practice, especially in those who are economically disadvantaged, have peripheral neuropathy, and have lived with diabetes for more than 10 years. (Curr Ther Res Clin Exp. 2022; 83:XXX–XXX)